Studi Anatomi Daun dari Tiga Anggota Suku Malvaceae di Kawasan Waduk Jatiluhur - Dorly, Dorly; Ningrum, Ratih Kusuma; Suryantari, Ni Kadek; Anindita, Fawzia La Rizma (Universitas Sebelas Maret, 2016)
Jatiluhur reservoir natural resort has miscellaneous vegetation, one of them is shrubs vegetation mostly found Malvaceae family. The purpose of this research was to study the diversity of anatomical structure of three members of Malvaceae family found in Jatiluhur reservoir area. Samples were leaf part of pungpulutan (Urena lobata), pulutan (Sida glutinosa), and sidaguri (Sida rhombifoliaa). Anatomical observations were carried out on the paradermal and transversal thin sections of microscopic preparation. Observation results of leaf paradermal preparation of the three plant species were anomositic stomata type were found on both sides of leaf (amphistomatic) with higher density on abaxial side than on adaxial side. Pungpulutan and pulutan have the same epidermis cell shape, wavy, while sidaguri has polygonal epidermis cell shape. On pungpulutan and pulutan were found non-glandular trichome type, whereas on sidaguri were discovered non-glandular and glandular trichome types. Observation results of leaf transversal preparation of three kinds of plants was found a layer of epidermis tissue. Palisade tissue of pungpulutan consisted of a layer of cells, while on pulutan and sidaguri the palisade tissue consisted of 3-5 layers of cells and 4-6 layers of cells subsequently.